KAJIAN KARAKTER FIKSI ARTHUR PENDRAGON DALAM PENDEKATAN LEVELS OF IDENTITY DAN HUBUNGANNYA DENGAN TRANSMEDIA STORYTELLING - Ken Natasha Violeta (ULTIMART Jurnal Komunikasi Visual, 2020)
The Transmedia Storytelling strategy is one of many strategies that support the sustainability of an entertainment media, one of which is the game. Games are a medium of interactive narrative entertainment. The three elements that support the narrative are time, character, and world-building. Sustainability through the transmedia character approach can be done by conducting a qualitative study. The writer takes the character of Arthur Pendragon, who examined the level of his identity to explain this character’s visual identity in a different universe.